2011
DOI: 10.1055/s-0030-1270743
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Antimicrobial Activities of Aporphine Alkaloids Isolated fromStephania venosa(Blume) Spreng

Abstract: The cytotoxic activity of five alkaloids, namely 4,5-dioxo-dehydrocrebanine (1), dehydrocrebanine (2), crebanine (3), oxostephanine (4), and thailandine (5) isolated from the tuber and leaves of Stephania venosa (Blume) Spreng was investigated. Thailandine showed the strongest activity against lung carcinoma cells (A549) (IC50 of 0.30 µg/mL) with very low cytotoxicity against normal embryonic lung cells (MRC-5). Thailandine also demonstrated strong activity against Plasmodium falciparum, K1 strain (IC50 of 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…Crebanine exhibits a variety of biological properties including, anti-microbial activities, improvement of neurodegenerative diseases, as well as antiinvasion and anti-proliferation activities in cancer cells. [14][15][16] Moreover, our previous report demonstrated that crebanine reduced TNF-α induced lung cancer cells proliferation and invasion via suppressing NF-κB activity.…”
Section: 13)mentioning
confidence: 96%
“…Crebanine exhibits a variety of biological properties including, anti-microbial activities, improvement of neurodegenerative diseases, as well as antiinvasion and anti-proliferation activities in cancer cells. [14][15][16] Moreover, our previous report demonstrated that crebanine reduced TNF-α induced lung cancer cells proliferation and invasion via suppressing NF-κB activity.…”
Section: 13)mentioning
confidence: 96%
“…20,21) Previous studies have shown that crebanine displayed cytotoxic and anti-cancer activities in many cancer cells, including A549 lung carcinoma cells, MCF-7 breast cancer cells, MOLT-3 lymphoblastic leukemic cells, and HL-60 cells. 13) However, the underlying mechanisms of this compound on growth inhibition are not well understood. The present study found that crebanine exerted significant growth inhibition effects on solid tumor and leukemic cells but had a slight effect on normal fibroblast cells.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of crebanine was elucidated by extensive spectroscopic analysis (UV, IR, MS, 1 H-NMR, 13 C-NMR) and the molecular formula was identified as crebanine, C 20 H 21 NO 4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15) Tubers of Stephania venosa (BLUME) SPRENG (S. venosa) have been used in traditional medicine in nerve tonics, aphrodisiacs, appetizers, and to treat asthma, microbial infection, hyperglycemia, malaria and cancer. 16,17) This genus is also well known as a rich source of alkaloids which exhibit a variety of pharmacological activities including being an antioxidant, as well as being antiarrhythymic, and contributing to the antiproliferation of cancer. 18,19) From our previous study, we demonstrated that crebanine from S. venosa induced cancer cell apoptosis and cell cycle arrest.…”
mentioning
confidence: 99%